Analysis Of The Significance Of Urea Nitrogen Levels In Milk And Blood In Dairy Cattle (Journal of Namibian Studies : History Politics Culture, 2023)
The determination of urea nitrogen levels in blood and milk is considered an alternative to determining the protein balance of dairy cattle. The ratio of rumen-degradable and non-rumen-degradable proteins is the origin of ammonia production, which is transformed into urea by the liver, circulates in the blood, and is partially excreted in the milk. The detoxification of ammonia constitutes a loss of energy for the dairy cow which limits milk production. The use of Yucca shidighera plant extract helps to retain the ammonia released in the rumen and increases its utilization by the microflora, limiting the increase of urea nitrogen in blood and milk.